An empirical evidence of the relationship between graduate interns’ capabilities on the successful of knowledge transfer programme in Malaysia - Rosle Mohidin; Roselina Ahmad Saufi; Roslinah Mahmud; Zatul Karamah A.B.U.; Mariam Firdhaus Mad Nordin (Asian Academy of Applied Business, 2017)
A spirit of collaborative partnership among universities, industries, and communities is a prerequisite for a success of knowledge transfer programme initiatives. The effort provides a platform for exchange of ideas either tangible or intangible, expertise, explicit or implicit knowledge and skills among parties involved. Companies are now beginning to recognize the fundamental value of knowledge transfer mechanism on how it is acquired, used and shared which contribute to their core competencies and in making sound strategic decisions to maintain the competitive advantage in today’s business environment. As to promote the ideas of knowledge transfer, the Ministry of Education (MOE) Malaysia has underlined the graduate interns’ capability as one of the areas under the critical agenda which need to be addressed in portraying the success of the knowledge transfer programme (KTP). Therefore, in order to obtain deeper insights of the issue, this project attempts to examine the contribution of graduate intern capabilities towards the success of KTP project in Malaysia. This study has employed a questionnaire that has been distributed to academics in the public universities in Malaysia who have obtained KTP grants from the government. The study has revealed that graduate interns’ capabilities contribute significantly to the implementation of knowledge transfer projects. Thus, higher education institutions must then address and review its present teaching and learning delivery to enhance students’ capabilities in dealing with the industry as well as with community.